POTRET PETUALANGAN NOVEL ANAK-ANAK MERAPI KARYA BAMBANG JOKO SUSILO KAJIAN SOSIOLOGI SASTRA - Okta Mahendra; Yasnur Asri; Nurizzati Nurizzati (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this research is to describe the portrait of adventure the novel that take place in the Children's Merapi Joko Susilo Bambang bouquet of. This research is a qualitative study using descriptive methods, technical content analysis. The data of this study is the portrait of a character in a novel of adventure Kid trim work Joko Susilo Bambang trace elements based characterizations. Based on the research results that the main character in search of adventure father destroyed by the eruption of Mount Merapi in Yogyakarta. Adventures of main character portraits and adventure events that occurred when Father the search.